Fuzzy portfolio selection using fuzzy analytic hierarchy process - Tiryaki, Fatma; Ahlatcioglu, Beyza (ELSEVIER SCIENCE INC, 2009)
Financial problems have been the subject of much research. A widely used approach in recent work on these problems is the use of fuzzy set theory, where fuzzy terms are used to model the uncertain environments. The purpose of this work is to combine the fuzzy analytic hierarchy process (AHP) with the portfolio selection problem. More specifically, the decision-making problem is to decide which stocks are to be chosen for investment and in what proportions they will be bought. To do this, we first dealt with two constrained fuzzy AHP methods given by Enea and Piazza [M. Enea, T. Piazza, Project selection by constrained fuzzy AHP, Fuzzy Optimization and Decision Making 3 (2004) 39-62]. We revised the first of these methods, addressing some of its fallacies, and called it revised constrained fuzzy AHP method (RCFAHP). Then we applied these two methods, namely, RCFAHP and the second- method of Enea and Piazza (2004), to the problem of choosing stocks on the Istanbul Stock Exchange (ISE). The methodology used for the hierarchy construction is based on the paper of Satty et al. [T.L Saaty, P.C. Rogers, R. Bell, Portfolio selection through hierarchies, The journal of Portfolio Management (1980) 16-21]. In this paper, we show that both of the models provide both ranking and weighting information, via fuzzy AHP, to the investors in this financial scenario. Finally, we discuss the relative advantages and disadvantages of these methods in comparison to existing methods in the literature. (c) 2008 Elsevier Inc. All rights reserved.
Keywords: Fuzzy AHP; Portfolio selection; Decision analysis; Constrained fuzzy arithmetic; Fuzzy mathematical programming; Finance; EXTENT ANALYSIS METHOD; DERIVING PRIORITIES; DECISION-ANALYSIS; MODEL; RANKING; AHP; Computer Science